2003
DOI: 10.1046/j.1365-2044.2003.03412.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of difficult laryngoscopy in obese patients by ultrasound quantification of anterior neck soft tissue*

Abstract: We assessed patients after their return home following gynaecological surgery, using a daily electronic diary. Thirty-two females aged 27-77 years took part. After a hospital stay of 1-6 days (mean 2.3), they were given a pen-based electronic diary and asked to record symptoms and other data over one month. They also completed a questionnaire at the end of the study. Substantial effects on quality and duration of sleep, pain during both the night and day, interference with daily activities, energy, and ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
241
6
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(262 citation statements)
references
References 21 publications
9
241
6
6
Order By: Relevance
“…20 By using ultrasound to quantify anterior neck soft tissue at the level of the vocal cords, Erzi et al observed that morbidly obese patients in whom difficult laryngoscopy was encountered had more pre-tracheal soft tissue and a greater neck circumference than patients who experienced an uncomplicated laryngoscopy; pre-tracheal soft tissue thickness was [mean (SD)] 28 (2.7) mm vs 17.5 (1.8) mm, respectively (P \ 0.001) and neck circumference was 50 (3.8) cm vs 43.5 (2.2) cm, respectively (P \ 0.001). 21 Komatsu et al did not find increased pre-tracheal tissue to be a good predictor of difficult laryngoscopy in obese patients; 22 however, the patients in this study had a comparatively smaller neck circumference [43.5 (4.7) cm vs 44.3 (5.3) cm; P \ 0.5] in the difficult and easy laryngoscopy groups, respectively. Further studies are required to clarify the role of ultrasound and pre-tracheal adipose tissue quantification as a predictor of difficult laryngoscopy.…”
Section: Direct Laryngoscopy and Intubationcontrasting
confidence: 56%
“…20 By using ultrasound to quantify anterior neck soft tissue at the level of the vocal cords, Erzi et al observed that morbidly obese patients in whom difficult laryngoscopy was encountered had more pre-tracheal soft tissue and a greater neck circumference than patients who experienced an uncomplicated laryngoscopy; pre-tracheal soft tissue thickness was [mean (SD)] 28 (2.7) mm vs 17.5 (1.8) mm, respectively (P \ 0.001) and neck circumference was 50 (3.8) cm vs 43.5 (2.2) cm, respectively (P \ 0.001). 21 Komatsu et al did not find increased pre-tracheal tissue to be a good predictor of difficult laryngoscopy in obese patients; 22 however, the patients in this study had a comparatively smaller neck circumference [43.5 (4.7) cm vs 44.3 (5.3) cm; P \ 0.5] in the difficult and easy laryngoscopy groups, respectively. Further studies are required to clarify the role of ultrasound and pre-tracheal adipose tissue quantification as a predictor of difficult laryngoscopy.…”
Section: Direct Laryngoscopy and Intubationcontrasting
confidence: 56%
“…Pretracheal fat measurement is performed at the vocal cords; it is the mean value of the distance in millimeter (mm) between the skin and the trachea measured on the central axis and 15 mm on each side. In obese patients, a pretracheal soft tissue thickness [28 mm is a more accurate predictor of difficult laryngoscopy than thyromental distance, mouth opening, modified Mallampati score, upper teeth abnormality and obstructive sleep apnea [10]. 2.…”
Section: Us Assessment Of the Airwaymentioning
confidence: 99%
“…6 The measurement of pretracheal soft tissue at the level of the vocal cords was found to be good predictor of difficult laryngoscopy in Middle Eastern obese patients in Israel. 6 However, Komatasu et al could not replicate these findings in American obese patients. 7 The difference between the two observations has been postulated due to the difference in the fat distribution between ethnic groups.…”
Section: Predicting Difficult Intubationmentioning
confidence: 99%
“…8,9 Neck ultrasound measurements are found to be as accurate as MRI for quantification of fat depth. 6 In patients with sleep apnoea, upper airway ultrasonography has been used to visualise approximation of the tongue base posteriorly and inferiorly towards the hypopharynx to cause airway obstruction. 10,11 Pharyngeal or laryngeal pathology, such as tumours, abscesses or epiglottitis which may have a significant effect during airway management, are detected by the use of US scan.…”
Section: Predicting Difficult Intubationmentioning
confidence: 99%